2012
DOI: 10.4081/ijas.2012.e59
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and physicochemical profile of traditionalSalsicda toscanaduring storage

Abstract: The aim of this study was to evaluate the evolution during refrigerated storage of the main microbiological and physicochemical parameters of a traditional Italian fresh sausage, salsiccia toscana. The following parameters were analyzed at Days 0, 6 and 9 of storage: total aerobic mesophilic and psychrotrophic counts, Brochothrix thermosphacta, lactic acid bacteria, Pseudomonadaceae, Enterobacteriaceae, Escherichia coli, Micrococcaceae, yeasts and moulds, Salmonella spp., Listeria monocytogenes; pH, Aw, moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…External and internal mean colour parameters at different sampling times (t0, t3, t7 and t9, days) of experimental sausages, with (PCþ) and without (PC-) protective culture, stored at 7 C. TPC counts. These data are in agreement with those of Tremonte et al (2005), and lower than those reported by other authors (Kamdem et al 2007;Chiavaro et al 2008;Nuvoloni et al 2012) for Italian fresh sausages. Regardless of the good initial hygiene, PC-sausages reached at the end of the shelf life (t7) a TMC of almost 7 log CFU/g at abusive temperature.…”
Section: Microbial Evolutionsupporting
confidence: 92%
See 2 more Smart Citations
“…External and internal mean colour parameters at different sampling times (t0, t3, t7 and t9, days) of experimental sausages, with (PCþ) and without (PC-) protective culture, stored at 7 C. TPC counts. These data are in agreement with those of Tremonte et al (2005), and lower than those reported by other authors (Kamdem et al 2007;Chiavaro et al 2008;Nuvoloni et al 2012) for Italian fresh sausages. Regardless of the good initial hygiene, PC-sausages reached at the end of the shelf life (t7) a TMC of almost 7 log CFU/g at abusive temperature.…”
Section: Microbial Evolutionsupporting
confidence: 92%
“…Regardless of the good initial hygiene, PC-sausages reached at the end of the shelf life (t7) a TMC of almost 7 log CFU/g at abusive temperature. Indeed, total viable aerobic counts higher than 6 log CFU/g are usually reported for Italian fresh sausage after 7 days of storage (Tremonte et al 2005;Kamdem et al 2007;Chiavaro et al 2008;Nuvoloni et al 2012).…”
Section: Microbial Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by Cocolin et al (2004) in fresh sausages for mesophilic aerobic counts, lactic acid bacteria, staphylococci, and enterobacteria. Higher initial contamination of analogous products was found in previous studies (Torrieri et al, 2011;Nuvoloni et al, 2012). In contrast, lower concentrations of these microbial groups were observed when antimicrobials were used both in carcasses cleaning and sausage manufacture (Benson et al, 2014).…”
Section: Culture-dependent Enumerationsmentioning
confidence: 61%
“…Little is known about the volatile composition of some traditional cheeses during ripening considering the effect of external and inner parts, particularly for Conciato Romano cheese, where the body interacts with other components such as extra‐virgin olive oil, red wine, and aromatic herbs. No papers were found in literature about the aroma of this typical cheese and, only few studies were found about microbiological profile focused on bacterial evolution during aging . Delgado et al studied the volatile profile of a Spanish goat raw milk cheese called “Queso Ibores” at four stages of maturation (1, 30, 60, and 90 days) using solid‐phase micro‐extraction‐gas chromatography‐mass spectrometry (SPME‐GC/MS), but the study did not consider the changes during a longer aging period.…”
Section: Introductionmentioning
confidence: 99%